2019
DOI: 10.1002/eji.201847513
|View full text |Cite
|
Sign up to set email alerts
|

Activation of integrated stress response pathway regulates IL‐1β production through posttranscriptional and translational reprogramming in macrophages

Abstract: Immune cells sense and programme its cellular machinery appropriately to the environmental changes through the activation of cytoprotective adaptive pathway so-called the "integrated stress response (ISR)". However, the mechanisms implicated in ISR-induced protective responses are poorly understood. Here, we show that ISR activation by arsenite (Ar) results in suppression of IL-1β production in macrophages and inhibition of DSSinduced colitis in a murine model through a novel posttranscriptional and translatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…We performed mass spectrometry with M2 TAMs and observed that a cluster of stress-associated proteins were upregulated in MDMs-M2. Many of the differentially expressed proteins ( Figure 2 A) were mainly involved in integrated stress response (ISR), especially SG assembly [ 37 , 38 ]. SG formation was triggered by SG nucleator proteins, such as G3BP1.…”
Section: Resultsmentioning
confidence: 99%
“…We performed mass spectrometry with M2 TAMs and observed that a cluster of stress-associated proteins were upregulated in MDMs-M2. Many of the differentially expressed proteins ( Figure 2 A) were mainly involved in integrated stress response (ISR), especially SG assembly [ 37 , 38 ]. SG formation was triggered by SG nucleator proteins, such as G3BP1.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of stress granules in leukocytes is part of the broader cellular response to inflammatory signals, and it contributes to the regulation of gene expression and the control of immune responses [ 108 ]. For instance, Tia-1 and TIAR-mediated recruitment of IL-1β to SGs suppressed the cytokine expression [ 109 ]. SGs prevent excessive innate immune activation protecting lymphocytes from TNFα/NFκB induced cell death [ 110 ].…”
Section: Stress and Are-bps In The Development Of Lymphoid Malignanciesmentioning
confidence: 99%
“…Likewise, translationally stalled IL-1β mRNAs recruit TIA1 and TIAR, resulting in RBP-RNA SG complexes. The SG pathway regulates IL-1β production, and bound IL-1β mRNAs might undergo degradation through the induction of autophagy [ 108 ]. TIAR is also a component of the RNP in the control of endotoxin-induced macrophage responses [ 109 ].…”
Section: Phylogenetics and Cellular/tissular Expression Profilingmentioning
confidence: 99%